Maternal mortality burden study from direct causes. Cuba, 2005-2018 - Lisbeth Fernández González; José Luis Peñalvo; Armando Humberto Seuc Jo; Delia María Gálvez Medina; Armando Rodríguez Salvá; Alain Francisco Morejón Giraldoni (Medisur)
Background: complications during pregnancy, childbirth and the puerperium are the main causes of death in women of childbearing age. The study of the mortality burden derived from these complications is useful to quantify the impact of premature deaths on the population life expectancy. Objective: to describe the behavior of the maternal deaths burden due to direct causes in Cuba, between 2005 and 2018. Methods: descriptive study of annual series, cross-sectional. The universe was the total of direct maternal deaths (N = 463). The mortality ratio, years of life potentially lost due to mortality, the trend, the percentage and the average were calculated. Results: during the years 2005-2018, 463 women died in Cuba from direct obstetric causes. Premature deaths quantified 22897 years of life lost due to this cause, with a tendency to decrease over time and with an annual average of 1636 years of life potentially lost; on average, they stopped living for each deceased, 49 years. The group of complications related to the puerperium (6790) was the direct cause that generated more years of life lost. Conclusion: the causes with the greatest impact on life expectancy were complications related to the puerperium, other hemorrhages and ectopic pregnancy; but the women who died at younger ages were from abortion and puerperal infection. Puerperal infections, placental disorders, and other complications tended to increase over time.